Analisis Faktor Risiko Kejadian Gout Arthritis pada Lansia - Angelia, Ninuk; Suciliyana, Yolinda; S, Ayu Kurnia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the prevalence of gout arthritis and identify risk factors contributing to its incidence in the Sokaraja Community Health Center I work area. A correlational approach was used to analyze the relationship between gender, nutritional status, diet, and physical activity level with the risk of gout arthritis in the elderly population in the area. The results showed no statistically significant association between the risk factors, with a p-value > 0.05. Based on the analysis, it can be concluded that the incidence of gout is not significantly associated with food type, physical activity, nutritional status, or gender. Although these four factors are often associated as potential risk factors, this study did not statistically demonstrate an effect on the incidence of hyperuricemia in older people in the Sokaraja Community Health Center I work area. Keywords: Physical Activity, Gout, Gender, Food Type, Nutritional Status